2012
DOI: 10.1088/0964-1726/21/3/035012
|View full text |Cite
|
Sign up to set email alerts
|

Towards holonomic electro-elastomer actuators with six degrees of freedom

Abstract: Functionally efficient six degree of freedom (DOF) actuators have not yet been developed in a scale-invariant and inherently compliant unified form. This has primarily been due to the use of conventional serial or parallel kinematical configurations and electromagnetic motors, pneumatics and hydraulics. Contrary to traditional technologies, utilizing electro-active elastomers enables multi-DOF actuation and holonomic operation with minimal structural complexity. Conical dielectric elastomer actuators (DEAs) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 24 publications
3
58
0
Order By: Relevance
“…The kinematics of the convex conical 5 degree of freedom actuator has recently been studied by Conn and Rossiter 49,50 (Fig. 9), an actuator that can be manufactured using print technology.…”
Section: Multi-degree-of-freedom De Actuationmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinematics of the convex conical 5 degree of freedom actuator has recently been studied by Conn and Rossiter 49,50 (Fig. 9), an actuator that can be manufactured using print technology.…”
Section: Multi-degree-of-freedom De Actuationmentioning
confidence: 99%
“…They have shown how this rotation can be achieved on a planar actuator using a non-uniform curved electrode patterning. 50 DE artificial muscles provide an attractive mechanism for multi-freedom devices that are fully soft and flexible with no rigid framework. Potz et al 43 demonstrated a soft rolling robot consisting of an inflated elastomer cylinder with an electro-active skin in four segments.…”
Section: Multi-degree-of-freedom De Actuationmentioning
confidence: 99%
“…This double cone DEA design, as applied by [5] and [6], consists of two single DE membranes stretched over a rigid rod in the center which maintains the tension. The two single conical DEA membranes can be actuated separately to produce bidirectional actuation.…”
Section: Modular Double Cone Dea Designmentioning
confidence: 99%
“…In nature, groups of muscles are typically configured to work antagonistically to perform multi-DOF movements. Taking inspiration from this, many multi-DOF DEAs have been developed: [4] produced a spring roll design with two DOF and a 5 DOF cone DEA is proposed by [5] and [6], which can be extended this into a 6 DOF elastic cube actuator [7].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism can generate a mono- directional or bidirectional movement. As an extension of this linear actuator a six degree of freedom conical DEAs is established to produce rotational actuation outputs which can be exploited in minimally invasive medical devices [12]. Those proposed mechanisms, which are flexible and have a high energy density, show promising properties in various applications.…”
Section: Introductionmentioning
confidence: 99%